Distal Arthrogryposis and Lethal Congenital Contracture Syndrome – An Overview - Desai, Darshini; Stiene, Danielle; Song, Taejeong; Sadayappan, Sakthivel (Frontiers in Physiology, 2020)
Distal arthrogryposis (DA) is a skeletal muscle disorder which can be classified under a broader term as Arthrogryposis multiplex contractures. DA is characterized by the presence of joint contractures at various parts of the body, particularly in distal extremities. It is identified as an autosomal dominant and a rare X-linked recessive disorder associated with increased connective tissue formation around joints in such way that immobilizes muscle movement causing deformities. DA is again classified into various types since it manifests as a range of conditions representing different etiologies. Myopathy is one of the most commonly listed etiologies of DA. The mutations in sarcomeric protein-encoding genes lead to decreased sarcomere integrity, which is often associated with this disorder. Also, skeletal disorders are often associated with cardiac disorders. Some studies mention the presence of cardiomyopathy in patients with skeletal dysfunction. Therefore, it is hypothesized that the congenitally mutated protein that causes DA can also lead to cardiomyopathy. In this review, we will summarize the different forms of DA and their clinical features, along with gene mutations responsible for causing DA in its different forms. We will also examine reports that list mutations also known to cause heart disorders in the presence of DA.